(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Cyperus difformis L. is a Cyperaceae, annual, of natural occurrence in marshy environments in southern Brazil, considered a weed in irrigated rice crops. Studies on its development are scarce, especially regarding its cycle and thermal requirements. Therefore, the objective of this work was to determine the base temperature, the thermal sum and the duration of the different sub-periods of the biological cycle of the species. The experiment was carried out at the Campus of the Universidade Federal de Santa Maria – UFSM, Santa Maria, Rio Grande do Sul, in four sowing seasons. In a completely delineated design and factorial scheme involving five soil water conditions (water depth and 50% soil water retention capacity [WRC]) from the sowing, water depth and 50% WRC introduced 21 days after emergence and 100% WRC during the whole cycle, with six repetitions each. Each experimental unit consisted of a cultivated in pot plant with 11 L capacity filled with soil. The cycle of the plants was subdivided into the sowing-emergence sub-periods, emergence-emission of the floral tassel and emission of the floral-maturing physiological tassel, being estimated the thermal requirements for the species. The conditions of the soil water condition the base temperature, the sum of the degree-days and the duration of the species cycle. The base temperature varies for each treatment, the sum of degrees-day decreases with the water deficit and the plants under flood accelerate the biological cycle.